Blocks of molybdenum ditelluride: A high rate anode for sodium-ion battery and full cell prototype study. (October 2019) - Panda, Manas Ranjan; Raj K, Anish; Ghosh, Arnab; Kumar, Ajit; Muthuraj, Divyamahalakshmi; Sau, Supriya; Yu, Wenzhi; Zhang, Yupeng; Sinha, A.K.; Weyland, Matthew; Bao, Qiaoliang; Mitra, Sagar
Abstract: Sodium-ion batteries (SIBs) are considered next-generation rechargeable batteries for grid-scale energy storage applications. This is because sodium is abundant in nature, and SIBs display electrochemical behavior that is similar to lithium-ion batteries (LIBs). Several high-performance sodium-rich cathode materials have been developed, which show excellent electrochemical performance. Nevertheless, the large-scale application of the ultimate metal-free sodium-ion battery that has a full cell configuration is hampered due to unavailability of reliable anode materials. We demonstrated a two-dimensional (2D), layered structured molybdenum di-telluride (MoTe2 ) as anode material in SIBs through this work. MoTe2 has been synthesized through a facile solid-state reaction route, and it has been used as an anode material without further surface modification or any conductive-coating carbon additives. Synchrotron X-ray diffraction (SXRD) and high-resolution scanning transmission electron microscopy (HRSTEM) confirm the hexagonal structure of MoTe2, which has the space group, P 63 / mmc . In a half-cell configuration (with respect to sodium metal), the MoTe2 electrode exhibits an initial specific capacity of 320 mA h g −1  at a current density of 1.0 A g −1, and it retains a high capacity of 270 mA h g −1 after 200 cycles. To detect the phase changes during sodiation/desodiation process and to explore the underlying sodium storage mechanism, SXRD, HRTEM with SAD, X-ray photoelectron spectrodcopy (XPS), X-ray absorption near edge structure (XANES) in ex situ mode along with in situ electrochemical impedance spectroscopy (EIS) and quantitative electrochemical kinetic calculations have been used. Further, a sodium-ion full cell is constructed by coupling the MoTe2 as anode and sodium vanadium phosphate Na3 V2 (PO4 )3 (NVP) as cathode. The sodium-ion full cell retains 88% of its initial capacity after 150 cycles at a current density of 0.5 A g −1 . Operating at an average potential of ~2 V, the full cell delivers a high energy density of 414 W h kg −1 . The present study opens up a new direction to the anode materials for rechargeable sodium-ion batteries. Graphical abstract: Image 1 Highlights: MoTe2 blocks with high purity hexagonal phase have been synthesized through a facile solid-state synthesis route. The as-synthesized MoTe2 is used as an active material for sodium-ion battery without any further surface modification or any conductive coating. Synchrotron X-ray diffraction (SXRD) and X-ray absorption near edge structure (XANES) are used to detect the phase changes during sodiation/desodiation process and to explore the sodium storage mechanism. A full-cell sodium-ion battery has been demonstrated using MoTe2 anode and sodium vanadium phosphate (NVP) as cathode. Operating at an average nominal potential of ~2 V, the full-cell delivered a high energy density of 414 W h kg −1 at a current rate of 0.5 A g −1 .